2014
DOI: 10.1093/aje/kwu137
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Time Interval Between Exposure to the World Trade Center Disaster and Incident Diagnoses of Obstructive Airway Disease

Abstract: Respiratory disorders are associated with occupational and environmental exposures. The latency period between exposure and disease onset remains uncertain. The World Trade Center (WTC) disaster presents a unique opportunity to describe the latency period for obstructive airway disease (OAD) diagnoses. This prospective cohort study of New York City firefighters compared the timing and incidence of physician-diagnosed OAD relative to WTC exposure. Exposure was categorized by WTC arrival time as high (on the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…In 2011, we showed that early arrival time at the WTC‐site was significantly associated with scoring at high risk for obstructive sleep apnea (OSA) using an adapted Berlin screening survey [Webber et al, ]. In a later study, we confirmed that 89% of 636 participants who scored high risk for OSA had polysomnogram‐confirmed OSA [Glaser et al, ]. We also found that FDNY rescue/recovery workers who arrived at the WTC during the morning of 9/11 had almost twice the odds (OR: 1.91; 95%CI: 1.15–3.17) of polysomnogram‐confirmed OSA than those with lower levels of WTC‐exposure.…”
Section: Researchmentioning
confidence: 56%
“…In 2011, we showed that early arrival time at the WTC‐site was significantly associated with scoring at high risk for obstructive sleep apnea (OSA) using an adapted Berlin screening survey [Webber et al, ]. In a later study, we confirmed that 89% of 636 participants who scored high risk for OSA had polysomnogram‐confirmed OSA [Glaser et al, ]. We also found that FDNY rescue/recovery workers who arrived at the WTC during the morning of 9/11 had almost twice the odds (OR: 1.91; 95%CI: 1.15–3.17) of polysomnogram‐confirmed OSA than those with lower levels of WTC‐exposure.…”
Section: Researchmentioning
confidence: 56%
“…The change points are the times that the relative rates change (increase or decrease) during the follow-up period; these change points are estimated from the data using profile likelihood. 21 , 22 , 23 A change point after which relative incidences did not differ significantly (p<0.05) from one would show that the exposure-response relationship between WTC exposure intensity and incident OAD was limited to the period prior to the change point. All models included as covariates: age on 9/11/2001, retirement status, if applicable, as a time-dependent predictor, and self-reported smoking status (ever vs. never) as of the last completed questionnaire.…”
Section: Methodsmentioning
confidence: 98%
“…Details of the methodological approach have been reported previously. 21 Briefly, we used piecewise exponential survival models with change points to estimate relative rates across the three exposure groups during follow up (9/11/2001 to 9/10/2011). Piecewise exponential survival models are similar to Cox regression models, but with baseline hazards that are allowed to change at a fixed number of time intervals rather than with every new event.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that FDNY WTC rescue/recovery workers were more frequently diagnosed with OAD than CRS in the months and years after exposure, but that over time, diagnoses of CRS increased ( 2 , 3 , 15 ). Similarly, about 6 years postexposure, GERD diagnoses, which had the lowest immediate post-9/11 incidence of these aerodigestive conditions, started to increase (unpublished data).…”
Section: Introductionmentioning
confidence: 94%